The effect of thriphala, a herbal Ayurveda formulation, on serum lipids, in patients on a maintenance dose of atorvastatin for hyperlipidaemia: a randomized controlled trial. - Ekanayaka, RAI; Rupasinha, ADCS; Sooriyarachchi, M.R.; Goonaratna, C. (My University, 2017)
Introduction Thriphala, a herbal medicinal formulation, is a bedrock of Ayurveda therapeutics with many postulated benefits. Objectives We performed a clinical trial to test the effects of Swastha Thriphala®, a proprietary preparation of thriphala, on serum lipid parameters in patients receiving atorvastatin. Methods Consenting adults receiving a maintenance dose of atorvastatin 10mg (Atorlip®) daily from a clinic of the Institute of Cardiology, National Hospital of Sri Lanka for lipid regulation, were randomly assigned, after counselling, to receive either the proprietary herbal medicinal product Swastha Thriphala® (Treatment Group, n= 101) or a placebo (Control Group n= 97), at the stipulated dose daily, for three calendar months. Results In the treatment group (n=101) the addition of a proprietary preparation of thriphala formulated as caplets of Swastha Thriphala®, in the standard daily dosage for three months, as an adjunct to atorvastatin 10mg, had a significant (p<0.0001) reduction in the mean total blood cholesterol, mean cholesterol/HDL ratio (p<0.0001), and mean non- HDL-cholesterol (p<0.0001) when compared to the Control Group (n=97) receiving placebo caplets in the same daily dose, with atorvastatin 10mg, for the same period. In the Treatment Group mean HDL, LDL, HS-CRP, and triglyceride concentrations showed non-significant reductions, and nonsignificant elevations in the Control Group. Conclusions Swastha Thriphala® when used in the stipulated dosage as an adjunct to atorvastatin 10 mg daily, significantly enhances its cholesterol reducing action in patients. The use of Swastha Thriphala® as single therapy for lipid regulation, and the mode of its action deserve investigation.